The Audience Reception and AI in the Political Campaign of the 2024 Bali District Heads Election - A.A.A. Ngurah Sumitha Ghanjali (Universitas Multimedia Nusantara, 2024)
Artificial Intelligence (AI), often referred to as artificial intelligence technology, is a new technology used to help solve various human needs in various aspects. One of these aspects is related to politics. With the existence of AI, political contestation is increasingly colourful and provides a new perspective for the community. The purpose of this study is to analyse the audience's reception of the use of artificial intelligence (AI) in political campaigns in the 2024 Bali district heads election using Stuart Hall's theory. The Encoding-Decoding process becomes the reference of this research in understanding how campaign messages poured through AI technology are received, interpreted, and consumed by audiences with diverse social and cultural backgrounds. This research uses a qualitative approach with in-depth interviews, observation, and analysing documentation to explore Balinese audiences' views on the use of AI in political campaigns. The main focus of this research is to understand how Balinese people with strong socio-cultural characteristics can adapt and interpret political messages delivered through various AI-based media tools and whether this understanding is in accordance with the intention of the sender of the message or there are influences from local factors. The results show that there are different ways in which Balinese audiences interpret AI-based campaign messages. There is a positive acceptance due to easy, fast and relevant access to information. However, on the other hand, there is a sense of concern about deprivation of privacy and manipulation of opinions. The findings are expected to provide insights into how AI-based technology can influence the dynamics of political communication through campaigns. In addition, this research also emphasises the need to increase media literacy both conventionally and digitally in order to be more critical in receiving political messages received, one of which is through AI. Keywords: Artificial Intelligence; political campaign; reception theory